استراتيجية إقامة الجولة العربية لزيادة الدافعية في تعلم مهارة الكلام لدى طلاب دار اللغة العربية والفقه السلفي بمعهد النقاية الإسلامي بمنطقة لاتي: The Implementation Strategy of Jaulah ‘Arabiyah to Enhance Learning Motivation in Speaking Skills (Mahārat al-Kalām) among Students of Darul Lughah Al-‘Arabiyah wa Al-Fiqh As-Salafi Annuqayah Latee Islamic Boarding School - Masturi Masturi; Kamal Yusuf; Umi Hanifah; Alif Alvian Mawaddi Hamid; Moh. Al Fayyadh (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2025)
Learning speaking skills is an essential aspect in Islamic boarding schools, particularly at Darul Lughah Al-‘Arabiyah wa Al-Fiqh As-Salafi Annuqayah Latee. However, many students are not motivated to develop speaking skills because they feel bored with the learning content, which hinders the process. While many studies have explored learning motivation, little research has focused on the implementation strategy of Arabic competition, especially in this pesantren. This study aims to examine the implementation strategy of Arabic competition and to identify the supporting and inhibiting factors affecting its practice. A qualitative field research design with a descriptive approach was employed, using observations and interviews with mentors and students. Data were analyzed through data reduction, display, and conclusion drawing to obtain a comprehensive understanding of the practice. The findings show that the implementation of Arabic competition consists of three stages: preparation, implementation, and evaluation. Although both supporting and inhibiting factors were found, the supporting factors were more dominant in increasing students’ motivation to speak Arabic. This research contributes to the study of Arabic language learning strategies in Islamic boarding schools and offers a practical model that can be adapted to increase motivation to speak Arabic. دراسة مهارة الكلام من الجوانب المهمة في التعليم داخل المعاهد الإسلامية، خاصة في دار اللغة العربية والفقه السلفي النقاية لاتي. ومع ذلك، فإن العديد من الطلاب غير متحفزين لتطوير مهارة الكلام لأنهم يشعرون بالملل من محتوى التعلم، مما يعيق العملية التعليمية. على الرغم من وجود العديد من الدراسات التي تناولت دافعية التعلم، إلا أن القليل منها ركّز على استراتيجيات إقامة المسابقة العربية، وخصوصًا في هذا المعهد. تهدف هذه الدراسة إلى دراسة استراتيجيات إقامة المسابقة العربية، بالإضافة إلى دراسة العوامل المساعدة والمعوقة في إقامتها. تم استخدام تصميم بحثي ميداني نوعي بالنهج الوصفي، من خلال الملاحظة والمقابلات مع المشرفين والطلاب. وتم تحليل البيانات عبر خطوات تقليص البيانات، وعرضها، واستنتاج النتائج للحصول على فهم شامل للممارسة. أظهرت نتائج البحث كما يلي: إقامة المسابقة العربية بدار اللغة العربية والفقه السلفي لها المراحل الثلاثة: المرحلة الاستعدادية والمرحلة الإجرائية والمرحلة التقييمية، وإقامة المسابقة العربية لزيادة الدافعية في تعلم مهارة الكلام لها العوامل المساعدة والمعوّقة، والعوامل المساعدة لها تأثير إيجابي أكثر بالنسبة من العوامل المعوّقة. تسهم هذه الدراسة في إثراء بحوث استراتيجيات تعليم اللغة العربية في المعاهد الإسلامية، وتقدّم نموذجًا عمليًا يمكن تكييفه لتعزيز دافعية مهارة الكلام في اللغة العربية.